Evaluation of Socialization and Promotion Activities at Open and Distance State University - Budiman, Rahmat; Wiradharma, Gunawan; Harsasi, Meirani; Riana, Kurnia Endah; Riady, Yasir (Journal of Social Work and Science Education, 2023)
Promotional activities are essential to offer special programs so it would be more valuable for the community towards the university. Promotion is one of the determining factors for the success of a marketing program in universities. This study aimed to describe how open and distance institution carries out promotional activities. Therefore, it can be seen as a promotional activity that effectively increases the number of new students. The research methodology used was descriptive qualitative. The data collection technique was carried out by in-depth interviews. This research was conducted online and offline in regional offices of Mataram, Denpasar, Malang, Bandung, Semarang, Ambon, Manado, Makassar, Jakarta, Majene, and Lampung. This study evaluated promotional activities that can be used as input for further promotional activities. Socialization and promotion activities at open and distance institution affect the increase in the number of students, and several things, such as population, presence of competitors, and condition of the community, influence addition.